Adductor Canal Nerve Block versus Intra-articular Anesthetic in Knee Arthroscopy: A Single-Blinded Prospective Randomized Trial - Perry, Michael; LeDuc, Ryan; Stakenas, Steven; Wozniak, Amy; Francois, Audrice; Evans, Douglas (The Journal of Knee Surgery, 2023)
Effective perioperative pain control following knee arthroscopy allows patients to reduce narcotic intake, avoid side effects of these medications, and recover more quickly. Adductor canal nerve blockade (ACB) and intra-articular injection of local anesthetic have been described as adjuvant treatments for postoperative pain control following surgery of the knee. This study directly compares the effect of each of these treatment modalities. Patients undergoing knee arthroscopy were blinded and randomized to receive either an ACB (n = 60) or intra-articular injection of local anesthetic (IAB, n = 64). Outcome measures included patient reported visual analog scale (VAS) scores at 1, 2, 4, 8, 16, 24, 36, 48 hours and 1 week and total narcotic consumption at 12, 24, and 48 hours postoperatively. Student's t-tests were used to compare unadjusted VAS scores at each time point and use of postoperative pain medication between treatment groups. Adjusted VAS scores were estimated in a multivariable general linear model with interaction of time and treatment group and other relevant covariates. There were no statistically significant differences between the two groups in terms of gender, age, body mass index, and insurance type. ACB patients had significantly higher pain scores than IAB patients at hours 1 and 2 (hour 1: 4.02 [2.99] vs. 2.59 [3.00], p = 0.009; hour 2: 3.12 [2.44] vs. 2.17 [2.62], p = 0.040). ACB patients had higher pain scores than IAB patients up to hour 16, though hours 4 to 16 were not significantly different. Adjusted covariate analyses demonstrate an additional statistically significant reduction in pain score in the IAB group at hour 4. There were no differences in narcotic consumption. Intraoperative local anesthetic and regional ACB each provides adequate pain control following knee arthroscopy, and intraoperative local anesthetic may provide enhanced pain control for up to 4 hours postoperatively.Level of Evidence: Level 1 evidence, randomized control trial.
Keywords: knee; analgesia; arthroscopy